Effects of power variation on cycle performance during simulated hilly time-trials - Wells, M. S.; Marwood, S. (European Journal of Sport Science, 2016)
It has previously been shown that cyclists are unable to maintain a constant power output during cycle time-trials on hilly courses. The purpose of the present study is therefore to quantify these effects of power variation using a mathematical model of cycling performance. A hypothetical cyclist (body mass: 70 kg, bicycle mass: 10 kg) was studied using a mathematical model of cycling, which included the effects of acceleration. Performance was modelled over three hypothetical 40-km courses, comprising repeated 2.5-km sections of uphill and downhill with gradients of 1%, 3%, and 6%, respectively. Amplitude (5-15%) and distance (0.31-20.00 km) of variation were modelled over a range of mean power outputs (200-600 W) and compared to sustaining a constant power. Power variation was typically detrimental to performance; these effects were augmented as the amplitude of variation and severity of gradient increased. Varying power every 1.25 km was most detrimental to performance; at a mean power of 200 W, performance was impaired by 43.90 s (±15% variation, 6% gradient). However at the steepest gradients, the effect of power variation was relatively independent of the distance of variation. In contrast, varying power in parallel with changes in gradient improved performance by 188.89 s (±15% variation, 6% gradient) at 200 W. The present data demonstrate that during hilly time-trials, power variation that does not occur in parallel with changes in gradient is detrimental to performance, especially at steeper gradients. These adverse effects are substantially larger than those previously observed during flat, windless time-trials.